Tourist Characteristics and Perceptions in Natural Tourism Attractions: A Case Study of Batur Geopark, Bali - Sari, Ni Putu Ratna; AA Gde Raka Dalem; Anak Agung Putri Sri (Asian Journal of Management, Entrepreneurship and Social Science, 2025)
This study aims to analyze the characteristics and perceptions of tourists visiting Batur Geopark, Bali. Using a quantitative approach, data was collected through questionnaires distributed to 200 tourists. The findings reveal that natural attractions, such as the beauty of Lake Batur, mountain panoramas, and activities like trekking and camping, are the main factors driving tourists to visit the area. Tourist motivations are categorized into several groups, with the primary motivations being to enjoy nature, seek new experiences, and spend time with family or friends. Overall, tourists' satisfaction with the facilities and comfort in the area is rated as good, although there are some shortcomings in supporting facilities, such as public toilets. The study also suggests several measures to enhance sustainable tourism, such as preserving natural attractions from over-exploitation, conserving biodiversity, and developing tourism packages targeted at the younger generation. The findings are expected to provide insights for local tourism managers in designing policies that support the sustainable development of tourism in Kintamani. Keywords: tourist perception, tourist characteristic, natural tourism attraction, Batur Geopark